Design and analysis of an RF rectifying circuit upon integration with monopole and Fractal antennas - Ibrahim, R. (Institute of Electrical and Electronics Engineers Inc., 2017)
RFID tags are commonly used in the industry for tracking and managing assets. The long range of a RFID reader is essential for detection of the RFID tags. Due to this requirement, tags are powered by batteries which deplete over a period of time and cause an inconvenience in the process of RFID tags detection. Therefore, a rectenna architecture consisting of a seven stage Cockroft-Walton voltage multiplier rectifying circuit and two Fractal antennas have been individually developed to counter the usage of batteries in RFID tags. The rectifying circuit harvests the RF energy generated by Wi-Fi signals to produce a voltage output. This paper focuses on the performance of the rectenna architecture after its integration with an antenna. The performance of a Koch-curve Fractal antenna, a bended Koch-curve Fractal antenna and a microstrip monopole antenna has been evaluated by measuring the output voltage after integration with the rectifying circuit. The Koch-curve Fractal antenna outperforms its counterparts in terms of received signal strength and output voltage produced. Therefore, the rectifying circuit is integrated with the Koch-curve Fractal antenna and effectively tested for average path loss. Hence, the performance of the rectenna is more optimized with Fractal antenna as compared to a microstrip monopole antenna. © 2016 IEEE.